Family life when a parent is diagnosed with cancer: impact of a psychosocial intervention for young children. Issue 2 (12th December 2012) - Semple, C.J.; McCaughan, E.
Abstract When a parent is diagnosed with cancer it can have a profound impact on the family, especially the children. This paper reports on the experience of parental cancer for parents' and their children and the impact of a psychosocial intervention for young children whose parent has cancer. Using a qualitative design, data were generated from separate focus groups with children (n = 7) and parents (n = 6). One‐to‐one interviews were conducted with professionals delivering the intervention (n = 2). Findings indicated that parents are often the gatekeeper to how, when and the context in which children learn about parental cancer. Many parents expressed a lack of confidence and skills as they considered communicating with their children about cancer. Parents stated the need for professional input mainly due to changes in their children's behaviour. Children had a number of fantasies and misconceptions surrounding cancer. This psychological intervention normalized their experience of parental cancer. It also improved children's understanding of cancer and equipped them with coping strategies. Professionals perceived the intervention led to improved family communication and promoted discussion of emotions. Open communication is pivotal for children whose parents have cancer but parents need supported and resourced to promote family coping when diagnosed with cancer.